2005
DOI: 10.1021/jf050835z
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Trends of Polychlorinated Dibenzo-p-dioxins/Furans (PCDD/Fs) and Dioxin-like Polychlorinated Biphenyls (PCBs) in Spanish Commercial Fish and Shellfish Products, 1995−2003

Abstract: The polychlorinated dibenzo-p-dioxin (PCDD), dibenzofuran (PCDF), and polychlorinated biphenyl (PCB) contents of 123 Spanish commercial salmon, tuna fish, sardine, oyster, mussel, and clam samples from 1995 to 2003 were investigated. A significant decrease of dioxin and non-ortho PCB concentrations in the studied species was found over the years. The decrease was greater in the case of dioxins than in that of non-ortho PCBs, especially during the early years of the study. PCB and PCDD/F concentrations in the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 31 publications
2
23
1
2
Order By: Relevance
“…This suggests that the profile observed in our samples is caused by the profile in the sediment and particulate matter at the harvest location of the mussels, although there are no data available to confirm this. The profile reported by Gomara et al [29] on mussel samples from the Spanish market were very similar to our data. Bayarri et al [28] reported a different pattern (2,3,4,7,3,7,8-TCDF as almost the only PCDD/F congeners present) in mussels from the Adriatic Sea, which is characteristic for that location as was also observed in other fish.…”
Section: Congener Profile Analysissupporting
confidence: 92%
“…This suggests that the profile observed in our samples is caused by the profile in the sediment and particulate matter at the harvest location of the mussels, although there are no data available to confirm this. The profile reported by Gomara et al [29] on mussel samples from the Spanish market were very similar to our data. Bayarri et al [28] reported a different pattern (2,3,4,7,3,7,8-TCDF as almost the only PCDD/F congeners present) in mussels from the Adriatic Sea, which is characteristic for that location as was also observed in other fish.…”
Section: Congener Profile Analysissupporting
confidence: 92%
“…The levels found are similar to of the levels reported by the other European countries (Table 1) (Kiviranta et al, 2001;Schmid et al, 2002;Fernandez et al, 2004;Papadopoulus et al, 2004;Baars et al, 2004;Gomara et al, 2005;Fattore et al, 2006;Tard et al, 2007) ). The cow cheese samples were divided according to their country of origin, resulting in four composite samples.…”
Section: Levels Of Pcdd/fs and Dl-pcbs In Belgian Foodsupporting
confidence: 89%
“…Diet is estimated to account for the majority of human exposure to POPs (Gasull et al, 2011;Gomara et al, 2005;Llobet et al, 2003).…”
Section: Introductionmentioning
confidence: 99%